Trust, Perceived Behavioral Control, Perceived Value and Efect Moderation of Optimism-Pessimism Level on Behavioral Intention - Arbol, Dolfina Martila; Ramli, Abdul Haeba (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to test and analyze the effect of Trust, Perceived behavioral control and perceived value both partially and simultaneously on Behavioral Intention in Go Food inter-food application users and the moderating effect of optimism and pessimism levels. The research approach used in this research is quantitative research. The population in this study are consumers who use the Go Food food delivery application. Data was collected using the survey method by distributing questionnaires to respondents who had ordered through the Go Food food delivery application, ordered food using the Go Food food delivery application in the last 1 month and were in the Jabodetabek area. Questionnaires collected as many as 190 respondents, the data is then processed using multiple linear regression method. Results of data analysis performed with the help of SPSS tools. Based on the results of this analysis it is known that the variables Trust, perceived behavioral control and perceived value partially and simultaneously have a positive effect on Behavioral Intention in Go Food Inter-food applications. Most of the respondents felt that using the food delivery application provided added value for consumers in the form of ordering food activities to be more practical. This made respondents feel that the food delivery application provided benefits that helped activities become more effective and time efficient which strengthened their intention to use the application. Keywords: Behavioral Intention, Trust, Perceived Behavioral control, Perceived value, Optimism & Pessimism Level